2015
DOI: 10.1371/journal.pone.0137800
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Oxidant Activity of Amine-Pyridine-Based Iron Complexes Efficiently Kills Cancer and Cancer Stem-Like Cells

Abstract: Differential redox homeostasis in normal and malignant cells suggests that pro-oxidant-induced upregulation of cellular reactive oxygen species (ROS) should selectively target cancer cells without compromising the viability of untransformed cells. Consequently, a pro-oxidant deviation well-tolerated by nonmalignant cells might rapidly reach a cell-death threshold in malignant cells already at a high setpoint of constitutive oxidative stress. To test this hypothesis, we took advantage of a selected number of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…The analysis of these results revealed that the activity of the metal binding peptides was consistent with that observed for the ligands alone. 45 Thus, BP16 conjugates incorporating the (S,S′)-BPBP ligand were more active than the sequences bearing the Me2 PyTACN metal binding moiety. However, the conjugation of these ligands to BP16 decreased their activity.…”
Section: Cell Cytotoxicity Of Bp16 Conjugates Incorporating a Me2 Pytmentioning
confidence: 96%
See 1 more Smart Citation
“…The analysis of these results revealed that the activity of the metal binding peptides was consistent with that observed for the ligands alone. 45 Thus, BP16 conjugates incorporating the (S,S′)-BPBP ligand were more active than the sequences bearing the Me2 PyTACN metal binding moiety. However, the conjugation of these ligands to BP16 decreased their activity.…”
Section: Cell Cytotoxicity Of Bp16 Conjugates Incorporating a Me2 Pytmentioning
confidence: 96%
“…Moreover, biological analysis of Me2 PyTACN and (S,S′)-BPBP ligands have shown their ability to chelate intracellular labile Fe(II) in cancer cells and that the resulting redox-active complexes induce apoptosis through pro-oxidant mechanisms. 45 In this work we envisioned that the conjugation of these ligands to a CPP could facilitate their uptake into cancer cells increasing their activity. Recently, we described the undecapeptide BP16 as a CPP able to favor the translocation of biologically active compounds across the cell membrane.…”
Section: Design Of Metal Binding Peptidesmentioning
confidence: 99%
“…Pyrrolidine–pyridine ligands 6 and 7 (Scheme ), which have previously been shown to enhance ROS (peroxide) activation reactions upon binding to iron(II), display equipotency towards CSC‐enriched and CSC‐depleted breast cancer populations in vitro . In contrast, related aminopyridine ligand 8 (Scheme ), which is also capable of binding iron(II) and inducing ROS, displays preferential toxicity toward CSC‐depleted cells .…”
Section: Endogenous Metal‐containing Complexes As Redox Modulatorsmentioning
confidence: 99%
“…[19] In contrast, related aminopyridine ligand 8 (Scheme 3), which is also capable of binding iron(II) and inducing ROS,d isplays preferential toxicity toward CSC-depleted cells. [19] As the cytotoxicity of 6 and 7 is augmented upon pre-treatment with iron(II) chloride in the breast and pancreatic adenocarcinoma cell lines (MCF-7 and CAPAN-1, respectively), 6-a nd 7-induced cell death is proposed to result from their ability to bind intracellular iron(II) ions and generate active coordination iron(II) complexes inside cells. Furthers tudies in non-CSC lines showedt hat in the presence of an excess amount of iron(II) chloride, 6 and 7 induce high levels of intracellular ROS leading to caspase-dependenta poptosis.…”
Section: Endogenous Metal-containing Complexes As Redox Modulatorsmentioning
confidence: 99%
“…The development of CSC-potent agents is in its infancy, and most of the drug candidates undergoing preclinical or clinical trials are completely organic in nature [7]. Our group and others have recently shown that metal complexes are capable of potently and selectively killing CSCs (over bulk cancer cells) [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%